Examining Formative Assessment Practices: Effects On Students’ English Language Learning - Jabeen, Iqra; Shakur, Nighat (Annals of Human and Social Sciences, 2024)
The objective of this study is to implement formative assessment techniques upon BS level students of Sargodha university to help them to overcome their deficiencies and weaknesses in learning English as a foreign language. Foreign language learning is the persistent need of present time in all systems of education. Action research design was chosen for this participatory study that is assisted in evaluation by the self-reflective spiral model by Kemmis and McTaggart 2004. Qualitative research method is used to measure the respective outcome of learner’s English language competency. A qualitative student survey is also conducted to get the effective feedback of students’ learning output. The result advocated that formative assessment practices impact students’ learning positively as students average scores increased with the assistance of formative assessment. This study recommended the due role of formative assessments in enhancing students motivational level to learn English as a second language.